Preparation of poly(ethylene terephthalate)/layered double hydroxide nanocomposites by in-situ polymerization and their thermal property - Q. Jiao; W. Cui; Y. Zhao; H. Li; H. Liu; M. Zhou (eXPRESS Polymer Letters, 2012)
Terephthalate (TA) intercalated layered double hydroxides (LDHs) were synthesized using hydroxides as raw materials, and poly(ethylene terephthalate) (PET)/LDH nanocomposites with different contents of TA intercalated LDHs were prepared by in-situ polymerization. The structure, morphology and thermal property of PET/LDH nanocomposites were investigated. The TA intercalated LDHs were partially exfoliated and well dispersed in PET matrix. The PET/LDH nanocomposites exhibit enhanced thermal stability relative to pure PET, confirmed by the thermogravimetric analysis results. The results of differential scanning calorimetry suggest that LDH nanoparticles could effectively promote the nucleation and crystallization of PET.